The hnRNP Q-like gene is retroinserted into the B chromosomes of the cichlid fish Astatotilapia latifasciata - Carmello, Bianca O. [UNESP] (2017)
B chromosomes are dispensable elements observed in many eukaryotic species, including the African cichlid Astatotilapia latifasciata, which might have one or two B chromosomes. Although there have been many studies focused on the biology of these chromosomes, questions about the evolution, maintenance, and potential effects of these chromosomes remain. Here, we identified a variant form of the hnRNP Q-like gene inserted into the B chromosome of A. latifasciata that is characterized by a high copy number and intron-less structure. The absence of introns and presence of transposable elements with a reverse transcriptase domain flanking hnRNP Q-like sequences suggest that this gene was retroinserted into the B chromosome. RNA-Seq analysis did not show that the B variant retroinserted copies are transcriptionally active. However, RT-qPCR results showed variations in the canonical hnRNP Q-like copy expression levels among exons, tissues, sex, and B presence/absence. Although the patterns of transcription are not well understood, the exons of the B retrocopies were overexpressed, and a bias for female B+ expression was also observed. These results suggest that retroinsertion is an additional and important mechanism contributing to B chromosome formation. Furthermore, these findings indicate a bias towards female differential expression of B chromosome sequences, suggesting that B chromosomes and sex determination are somehow associated in cichlids.